Four key enablers of youth empowerment to achieve more sustainable agri-food systems - Panday, Dinesh (Young Professionals for Agricultural Development, 2023)
Our agri-food systems are facing increasing shocks and stresses, which puts them under immense pressure. This raises the question of whether we can produce efficiently to meet rising global demand, while protecting the environment and communities inclusively and more sustainably. For this question, it is necessary to adopt practices that can make agriculture and forestry more efficient under limited availability of natural resources. However, the key challenge is to transform current agri-food systems into more resilient, sustainable, equitable and accessible systems for all and it is essential to identify and support the main drivers of this transformation. The first cohort of Young Scientists Group (2022–2023) conducted a review, including case studies and an interview, on specific policy issues, of particular concern to youth, related to agri-food systems transformation. We explored that youth, including diverse groups such as rural youth, indigenous youth, young women, etc., are better positioned as drivers and agents of change by advancing four key enablers (education, technology, science and policy) especially given their willingness to take risks and adopt new ideas. The complete report is divided into five chapters: (i) provides an overview of the latest issues affecting agri-food systems, (ii) focuses on the challenges faced by youth who are working to advance sustainable agri-food systems, (iii) identifies and explores four key enablers of youth empowerment, (iv) highlights existing youth-based initiatives for improving agri-food systems, and (v) provides conclusions with 18 science-based and action-oriented recommendations that need to be adopted immediately to achieve more sustainable agrifood systems.